Physicochemical Analysis of Herbo-Mineral Medicine. (2018) - Kannan, N.; Balaji, S.; Anil Kumar, N.V.
Abstract: Annabhedi chendooram (ABC), iron based Siddha drug being extensively used for the treatment of anaemia, leucoderma, and spleen disorders. This study was aimed for the physicochemical fingerprint of commercially available ABC. The spectral identification of elements in the sample were evaluated using UV-visible spectrophotometer, X- ray diffractometer (XRD), energy dispersive X-ray analysis (EDX) and Fourier transform infrared spectrometer (FTIR). The morphology and surface characteristics were analyzed by scanning electron microscope (SEM), zeta potential and brunauer–emmett–teller (BET). Our investigation on ABC revealed the presence of 73.24 % Iron in oxides, complexed with organic compounds. Presence of organic group may enhance its absorption, digestion and pharmacological action. Further in detailed study is warranted to study the benefits of ABC over conventional iron drugs